Planning Consistency and the Political Budget Cycle in Indonesia - Khoirunurrofik, Khoirunurrofik; rahmawati, Farina (Jurnal Ekonomi Kuantitatif Terapan, 2021)
This study aims to find empirical evidence of the relationship between planning and the practices associated with political budget cycles in Indonesia, with reference to the simultaneous regional head elections held in 2017 and 2018. A fixed-effect method using least-square dummy variables analyzes the role of planning in the relationship between local-government spending and political budget cycle behaviors. The results indicate that consistency between planning and budgeting can control the discretion applied by regional heads to increase and decrease budget expenditure in the two years before an election, one year before an election and in the election year itself. The magnitude of these reductions or increases differs between types of expenditure. The association between planning and the political budget cycle is significant in the two years before an election for primary expenditure allocations and in a year before an election for allocations of capital expenditure, social assistance, and grants and subsidies.